2020
DOI: 10.1021/acschemneuro.0c00274
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Investigation of Metabolic Changes Occurring in the Rat Brain Hippocampus after Fluoxetine Administration Using Two Complementary In Vivo Techniques: Solid Phase Microextraction and Microdialysis

Abstract: Fluoxetine is among the most prescribed antidepressant drugs worldwide. Nevertheless, limited information is known about its definitive mechanism. Although in vivo examinations performed directly in related brain structures can provide more realistic, and therefore more insightful, knowledge regarding the mechanisms and efficacy of this drug, only a few techniques are applicable for in vivo monitoring of metabolic alterations in the brain following an inducement. Among them, solid phase microextraction (SPME) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
4
16
0
Order By: Relevance
“…Based on this nding, the lipidomic analysis was carried out using the C18 ber. This is consistent with the work of Boyaci et al 11 , who used the C18 sorbent for their lipidomics analysis, and a mixed-mode extractive phase for their metabolomics analysis.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Based on this nding, the lipidomic analysis was carried out using the C18 ber. This is consistent with the work of Boyaci et al 11 , who used the C18 sorbent for their lipidomics analysis, and a mixed-mode extractive phase for their metabolomics analysis.…”
Section: Discussionsupporting
confidence: 91%
“…SA1-SA4). Nonetheless, it is important to note that the range of extracted metabolites was still limited, and, consistent with the research conducted by Cudjoe et al and Boyaci et al, for instance neurotransmitters were not observed in untargeted analyses 10,11 . However, it is possible to extract neurotransmitters with SPME by optimizing the analytical protocol for that speci c group of substances 10,15 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations